The Preferred Reconstructive Choice for a Lower Third Tibial Exposure Defect: An Online Survey of 356 Microsurgeons - Čebron, Urška; AbdelRahman, Mohamed; Kwon, Soo-Ha; Lee, Che-Hsiung; Hsu, Angela Ting-Wei; Huang, Jung-Ju; Chen, Lisa Wen-Yu; Sung, Cheyenne Wei-Hsuan; Chang, Tommy Nai-Jen (Journal of Reconstructive Microsurgery, 2023)
Background One of the most challenging yet common areas in reconstructive surgery is the closure of defects in the lower leg. Surgeons can choose from several reconstructive options including local and free flaps. The aim of this study was to understand the reconstructive strategy for lower leg defects of different microsurgeons around the world by harnessing the power of social media and online questionnaires.Methods A case of a patient with an exposed plate over distal tibial fracture was presented via an online questionnaire distributed on various social media platforms. A total of 369 international microsurgeons replied with their preferred treatment choice. The data were analyzed according to geographic area, microsurgical training, seniority, and subspecialty.Results Among all the respondents (n = 369), 64% would have opted for a free flap reconstruction, while the remaining 36% would have opted for a local/pedicle flap. In the group that would have opted for a free flap, 63% would reconstruct the defect using a free fasciocutaneous flap, while the remaining 37% would have used a free muscle flap. In the local flap group, 60% would have used a local perforator while 30% would have chosen a conventional local flap. While North American and European microsurgeons had a clear preference toward free flaps, Asian, Middle Eastern, African, and South American surgeons were evenly divided between local and free flaps.Conclusion In this study, we provide a current global overview of the reconstructive strategies for a lower limb with skin defect and bone or prosthesis exposure. We hope that this will be able to help global microsurgeons and patients worldwide.
Keywords: microsurgery; lower limb reconstruction; survey